The Effect of Nutritional Therapy on Bone Mineral Density and Bone Metabolism in Pediatric Crohn Disease. Issue 6 (June 2021) - Lev-Tzion, Raffi; Ben-Moshe, Tehila; Abitbol, Guila; Ledder, Oren; Peleg, Sarit; Millman, Peri; Shaoul, Ron; Kori, Michal; Assa, Amit; Cohen, Shlomi; Strich, David; Revel-Vilk, Shoshana; et al.
ABSTRACT: Objectives: Both the inflammatory burden of Crohn disease (CD) and corticosteroids have a negative effect on bone density. Exclusive enteral nutrition (EEN) avoids corticosteroids and promotes endoscopic healing. We aimed to explore the effect of nutritional therapy on bone health in pediatric CD. Methods: This was a planned sub-study of a clinical trial enrolling children with new-onset mild-moderate CD. Children were randomized to either 6 weeks EEN followed by 6 weeks 25% partial enteral nutrition (PEN) or 6 weeks of 50% PEN with a CD exclusion diet followed by 6 weeks of 25% PEN with exclusion diet. Bone formation and resorption were measured at baseline, week 12 and week 24 by serum C-Propeptide of Type I Procollagen (CICP) and type I Collagen N-Telopeptide (NTX), respectively. Bone mineral density (BMD) was measured by dual energy X-ray absorptiometry (DXA) scan at baseline and week 24. Results: Median CICP improved from 130 ng/mL (106–189) at baseline to 223 (143–258) at week 12 and 193 (143–252) at week 24 ( P  = 0.016 for both, n = 29 children). Median NTX remained unchanged ( P  = 0.45 and P  = 0.45). Thirty-six children had DXA scans performed at diagnosis; 81% and 33% had z scores of <−1 and <−2, respectively. DXA z scores did not improve from baseline (adjusted total body less head [TBLH] BMD −1.62 ± 0.87) to week 24 (−1.76 ± 0.75; P  = 0.30, n = 21 with both scans). Conclusions: Low bone density is common in new-onset mild-moderate pediatric CD. CICP, a sensitive marker of bone formation, improved following dietary intervention but this was not associated with improved BMD.